Alkaloids from the rhizomes of Acorus calamus and their PPARα, PPARγ, and glucokinase-activating activities. (October 2021) - Hao, Zhi-You; Cao, Yan-Gang; Wang, Yan; Zhang, Chun-Lei; Luo, Huan; Liang, Dong; Liu, Yan-Fei; Chen, Ruo-Yun; Yu, De-Quan
Graphical abstract: Highlights: Fourteen alkaloids were isolated from Acorus calamus . Compound 1 was a new alkaloid and compound 3 was a new natural product. The absolute configurations of compounds 1 –2 were deduced by induced CD spectra. Compound 4 exhibited significant PPARα/γ, and glucokinase-activating activities. Molecular docking of compound 4 bound with PPARα, PPARγ, and GK was carried out. Abstract: Fourteen alkaloids of diverse carbon skeletons, including a new compound 2 R -4-(5′-methyl-pyrazin)-2-yl-but-3-ene-1, 2-diol (1 ) and a new natural product methyl 2-(4-hydroxyphenyl)acetyl glycinate (3 ), were isolated from the ethanol extract of Acorus calamus Linn. rhizomes. Their structures were determined based on extensive spectroscopic analyses and comparing of the literature data. Compounds 1 –5 were evaluated for their in vitro PPARα, PPARγ, and glucokinase-activating activities, and neotatarine (4 ) exhibited significant PPARα and PPARγ activating activities at 10 −6 mol/L, and it also exhibited significant glucokinase activating activities at 10 -5 mol/L. Furthermore, molecular docking of compound 4 bound with PPARα, PPARγ, and GK was carried out to investigate some possible structural insights into the potential binding patterns.